Idāratu Takhṭīṭ Barnāmij Al-Masraḥīyyah Fī Manẓūr Mahārāt Al-Qarni Al-Ḥādī Wa Al-ʿIsyrīn - Firman Nurul Fauzi; Zakiyah Arifa (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2023)
Managing the planning in the program, in turn, serves as a guide for defining the strategy you will implement. On the other hand, twenty-first (21st) century skills are one of the skills that can help program planning. This study aims to describe the planning Masrahiyah program in the Arabic language education department. The descriptive qualitative method is applied due to the research aims, with interviews, observation, and documentation as the data collection method. Data analysis used the Miles and Huberman method of following instructions and data, presenting the data, and summarizing or deducing. The results of this research are: 1) Masrahiyah program has two models, top-down and bottom-up, and SWOT analysis is used to set goals in this program. 2) From the twenty-first (21st) century skill perspective, the Masrahiyah showed that it has many skills, communication, creativity, and cooperation. There needed to be more using language for some students because of a lack of interest in using the Arabic language.